2009
DOI: 10.1002/apj.286
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of tetracycline in aqueous medium by electrochemical method

Abstract: The degradation of tetracycline by anode oxidation with Ti/RuO 2 -IrO 2 electrode was carried out in an electrochemical cell. The effect of operating conditions such as electrical current density, initial pH, antibiotic concentration, electrolyte concentration and hydroxyl radical scavenger on the oxidation of tetracycline was investigated. The results showed that the degradation of tetracycline followed apparent pseudo-first-order kinetics. The rate constant increased linearly with the current density, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 20 publications
3
26
0
2
Order By: Relevance
“…In two separate studies, Wu et al [22] and Zhang et al [23] studied the electrochemical degradation of TeC using a Ti/RuO 2 -IrO 2 anode in an aqueous solutions containing Na 2 SO 4 as the supporting electrolyte. The authors concluded that TeC can be efficiently removed by the electrooxidation process.…”
Section: Introductionmentioning
confidence: 99%
“…In two separate studies, Wu et al [22] and Zhang et al [23] studied the electrochemical degradation of TeC using a Ti/RuO 2 -IrO 2 anode in an aqueous solutions containing Na 2 SO 4 as the supporting electrolyte. The authors concluded that TeC can be efficiently removed by the electrooxidation process.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, many researchers tried to use chemical processes such as the photo-Fenton (Bautitz and Nogueira, 2007), electrochemical process (Zhang et al, 2009), ultrasound/goethite/O 3 (Wang et al, 2011) and ultrasound/Fe 3 O 4 /Na 2 S 2 O 8 (Hou et al, 2012) to degrade the tetracycline. Based on the results shown in above studies, the strength of introduced energy by ultraviolet (UV) light or ultrasound, additions of H 2 O 2 or iron-salts and pH affect the efficiency of tetracycline degradation.…”
Section: Introductionmentioning
confidence: 99%
“…With a growth of population, intensive agriculture and industrialization, a very important role today is played by clean water recovery processes from wastewater for reuse by elimination of antibiotics from terrestrial and aqueous resources. Several studies on degradation of tetracycline, using different technologies were conducted: using activated sludge processes [9], TiO 2 nanopore arrays electrode [10], TiO 2 and ZnO aqueous suspensions were also used in the photocatalytic oxidation of tetracycline, under simulated solar light [11], photocatalysis of TC with C-N-S tridoped TiO 2 material [12], electron pulse radiolysis [14][15][16][17], using Pt plates as anode [14], with Ti/RuO 2 anode [15]. In this study, the electrochemical reactions followed pseudo-first order kinetics.…”
Section: Introductionmentioning
confidence: 99%